Miao medicine Tiekuaizi (Radix Chimonanthi): a review of its traditional uses, phytochemistry, pharmacology, and predictive analysis on quality markers - Luo, Li-ying; Zhang, Xu-dong; Mei, Hui-min; Ma, Jian-hui; Peng, Xin; Dong, Ming-hong; Huang, Cong (Frontiers in Pharmacology, 2025)
Miao medicine Tiekuaizi (Radix Chimonanthi) have been successfully used by Guizhou Miao ethnic physicians in clinical treatments, demonstrating significant curative effects. The research progress on the resource distribution, traditional uses, phytochemistry, pharmacology of Tiekuaizi were reviewed by collecting related literature from traditional Chinese medicine books and various databases. Based on the comprehensive review, and centered around the principles of traditional Chinese medicine quality marker (Q-Marker) theory, nine secondary metabolites (scopoletin, scopolin, isofraxidin, fraxin, scoparone, calycanthoside, 6, 7, 8-trimethoxycoumarin, tomenin and calycanthine) are suggested as potential Q-markers for Tiekuaizi to establish quality control standards. This can provide valuable reference for the collection and processing, pharmaceutical production, effectiveness and safety of clinical applications of Miao medicine Tiekuaizi.